Comprehensive transcriptomic profiling reveals tissue-specific molecular signatures and dysregulated pathways in human diabetic foot ulcers - Hu, Guangrong; Nisar, Ayesha; Khan, Sawar; Li, Wen; Zhu, Enfang; Cui, Haoling; Zhang, Guiqin; He, Yonghan; Sun, Hui (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcers (DFUs) are a severe complication of diabetes mellitus characterized by impaired wound healing, chronic inflammation, and tissue degeneration. We sought to identify tissue specific molecular drivers of DFU pathogenesis across skin, adipose, and muscle compartments.MethodsHigh throughput RNA sequencing was performed on skin, adipose, and muscle tissues from DFU patients and non-ulcerated diabetic controls. Differential expression analyses and pathway enrichment were conducted to delineate common and compartment-specific transcriptional changes.ResultsAll DFU tissues exhibited a conserved upregulation of immune activation genes—including chemokines (CXCL1-8), cytokines (IL1B, IL6), and NF-κB pathway components—alongside downregulation of metabolic regulators (PPARG, ADIPOQ), oxidative phosphorylation genes (SDHA, NDUFS2), and insulin signaling factors (IRS1, AKT2). Skin showed increased keratinocyte proliferation and senescence markers (KRT16, FOXM1); adipose tissue revealed adipocyte dedifferentiation and elevated matrix protease activity (MMP9); and muscle displayed fibrotic remodeling and mitochondrial suppression (COL1A1, NDUFS7). Enrichment analyses implicated IL17 signaling, PPAR pathways, and cellular senescence as central disrupted processes.ConclusionDFUs are driven by a dual pathology of inflammatory amplification and metabolic shutdown, overlaid with distinct tissue-specific alterations. Key targets such as chemokine signaling, PPAR-mediated metabolism, and senescence factors emerge as promising candidates for precision therapies aimed at restoring inflammatory–metabolic balance and enhancing wound healing.